Las mil y una posibilidades de un cuento. - Martín Ambite, L.; Martín Ramos, S.; Martín Zambonino, P.; Rufiangel García, P.; Saiz Calvo, L.M.; Maroto Escudero, C. (Didáctica. Lengua y Literatura, 1994)
Sin resumen